CASE STUDY: Evolution of San Antonio's 311-Customer Relationship Management System. - FLEMING, CORY; STALLCUP, PAULA (Public Management (00333611), 2019)
The article focuses on evolution of the San Antonio's 311-Customer Relationship Management System as a new mobile app on August 15, 2018. Topics discussed include the app allowing residents to connect with local government for information and service requests, enhancing the channels available for citizens, and service level agreement (SLA) compliance.